2012
DOI: 10.1103/physreve.86.036606
|View full text |Cite
|
Sign up to set email alerts
|

Binding energy of soliton molecules in time-dependent harmonic potential and nonlinear interaction

Abstract: We calculate the binding energy of soliton molecules of an integrable nonlinear Schro[over ̈]dinger equation with time-dependent harmonic potential and cubic nonlinearity. Through a scaling transformation, an exact formula for the binding energy can be derived from that of the free soliton molecules in a homogeneous background. In the special case of oscillatory time dependence, sharp resonances occur at some integer and fractional multiples of the natural frequency of the molecule. Enhanced binding is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Various analytical methods are used to solve different versions of the NLSE such as the inverse scattering transform [86][87][88][89][90][91][92][93], the Adomian Decomposition method [94], the Homotopy Analysis method [95,96], the similarity transformation method [97][98][99][100][101][102], and the Darboux transformation and Lax pair method [103][104][105][106], just to name a few. This section is devoted to deriving the general breather solution of the fundamental NLSE using the Darboux transformation and Lax pair method [107].…”
Section: Analytical Derivation Of the Fundamental Peregrine Solitonmentioning
confidence: 99%
“…Various analytical methods are used to solve different versions of the NLSE such as the inverse scattering transform [86][87][88][89][90][91][92][93], the Adomian Decomposition method [94], the Homotopy Analysis method [95,96], the similarity transformation method [97][98][99][100][101][102], and the Darboux transformation and Lax pair method [103][104][105][106], just to name a few. This section is devoted to deriving the general breather solution of the fundamental NLSE using the Darboux transformation and Lax pair method [107].…”
Section: Analytical Derivation Of the Fundamental Peregrine Solitonmentioning
confidence: 99%
“…Soliton molecules (SM) attract significant fundamental and practical interest [1][2][3][4][5]. Previous decades of research revealed a plethora of soliton molecule types including: SM with independently evolving phase and flipping phase, group-velocitylocked vector SM [6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Through the GP equation with constant and oscillatory part of the contact interaction, Saito and Ueda stabilized the trapless matter-wave bright solitons in 2D by temporal modulation of contact interaction [48], Adhikari examined the problem and stabilized the untrapped soliton in 3D and the vortex soliton in 2D by temporal modulation of contact interaction [46]. Effects of the time-dependent nonlinear contact interaction on the binding energy of soliton molecules has been examined by Khawaja and Boudjemaa [47]. We have studied the stability of the 3D BEC with constant and oscillatory part for both the two-and three-body interactions in our previous work [45].…”
Section: Introductionmentioning
confidence: 99%